CATECHOL-O-METHYLTRANSFERASE (COMT) ENZYME LEVELS IN PATIENTS WITH PREOPERATIVE ANXIETY - Hamongan Nasution, Akhyar; Lelo, Aznan (Transpublika Publisher, 2022)
The preoperative anxiety’s incidence is very high and mostly preoperative patients have anxiety. It was found that low COMT levels indicate a tendency to develop anxiety. Hence, this study aims to investigate COMT enzyme levels in patients with preoperative anxiety. This research is a purely experimental research with a pretest-posttest control group design and double-blind. Measurement of COMT enzyme levels was executed by utilizing ELISA technique. Blood samples were taken from preoperative anxiety patients who were assessed with the Amsterdam Preoperative Anxiety Information Scale (APAIS). The research was carried out at Haji Adam Malik General Hospital and Regional General Hospital dr. Pirngadi Medan, and Integrated Laboratory of the Faculty of Medicine, University of North Sumatra. The were 64 samples involved in this research that fit the inclusion and exclusion criteria. The findings show that COMT levels in the anxiety and control groups had differences with p values ​​= 0.014. In addition, COMT levels in the preoperative anxiety group were lower when compared to those without the preoperative anxiety group, where in the anxiety group had COMT enzyme levels of 0,14 ± 0,08 ng/dl, while in the control group had higher COMT levels 0,96 ± 1,11 ng/dl. The results showed that patients with preoperative anxiety had lower levels of the COMT enzyme compared to patients without preoperative anxiety. Researchers suspect there is a role for the COMT enzyme in causing preoperative anxiety.